Auctions and fair division games: A cross-cultural bidding experiment - Radosveta Ivanova-Stenzel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
This paper presents the results of experiments carried out in two countries, Germany and Bulgaria, and for different allocation rules (first vs. second price auction vs. fair division game). The data analysis of the sealed-bid, private value-contests compares the bid function in both countries, some features of the bidding behavior (learning of risk neutral equilibrium bidding, truthful bidding, decision time, bid adjustments) as well as the efficiency rates and the price expectations. The main results obtained in Germany were replicated with the Bulgarian subjects.
urn:nbn:de:kobv:11-10047374
Keywords: D44; C92; O57; 330